Technical infrastructure of rural municipality of Nowa Sól in the light of sustainable development - Kostecki, Jakub; Kołodziejczyk, Urszula; Augustyniak, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sustainable development is synonymous with the coexistence of man and the world around him on equal rights. The progressing urbanization often leads to depletion of environmental resources and puts man above natural environment. The purpose of this paper is to analyse current situation and possibilities of development of technical infrastructure of rural municipality of Nowa Sól, the Province of Lubuskie, in the light of sustainable development.
Keywords: technical infrastructure; sustainable development; rural municipality